The Omani Experience of Multi-religious Coexistence and Dialogue: A Historical Approach to the Omani Principles and its Luminous Examples - Maawali, Al Muatasim (Journal of Islamic Thought and Civilization, 2021)
In a world that is increasingly hostile towards religious minorities, this paper tries to set a modern-day, successful example of multi-religious coexistence and interfaith dialogue. The paper examines historical examples derived from Omani history and explores Omani characteristics by surveying Western reports written by missionaries, visitors, and travellers of different religions in Oman. This is meant to demonstrate the hypothesis that the multi-religious coexistence and interfaith dialogue enjoyed today by the nearly fourmillion Omani population is a natural result of a long history of commitment to ‘Omani values’ and principles, practised by Oman’s Ibāḍī population with their fellow nonMuslims. The paper concludes that there is a strong correlation between the ‘Omani values’ recorded by the Western writers and the ongoing deeply rooted Omani experience of peaceful religious coexistence and interfaith dialogue. These ‘Omani values’ include the principles of tolerance, social justice, mutual respect, friendliness, hospitality, and simplicity. Finally, owing to the increasingly rising tensions between adherents of different religions, the paper recommends that such successful Omani experiences should be exported to other countries in the Muslim world and elsewhere. Keywords: Oman, Ibāḍīsm, multi-religions, coexistence, dialogue, tolerance